Numerical Study of Natural Convection Heat Transfer in Enclosure with Partition - ไวท์ยางกูร, สุพจน์ (KKU Science Journal, 2014)
In this research, we present the numerical study for natural convection heat transfer of steady flow within square enclosure with partition on the upper part of enclosure. Boundary condition, on thelower part and upper part are insulated wall. Here, the right vertical wall and partition are cooled while the left vertical wall is heated. The problem is studied for different values for Prandtl number, Rayleigh number and height of partition to compare the behavior of fluid flows.The numerical solutions are calculated by using FlexPDE 6.17 professional version and displayed in terms of isotherms and streamlines.